Rescue of Immunotherapy-Refractory Metastatic Merkel Cell Carcinoma With Conventionally Fractionated Radiotherapy and Concurrent Pembrolizumab - Bloom, Brooke C.; Augustyn, Alexander; Pezzi, Todd A.; Menon, Hari; Mayo, Lauren L.; Shah, Shalin J.; Schwartz, David L.; Chmura, Steven J.; Johnson, Faye M.; Welsh, James W.; Chun, Stephen G. (Frontiers in Oncology, 2019)
Merkel cell carcinoma has historically had dismal prognosis with limited cytotoxic chemotherapy options that provide durable control of metastatic disease. The advent of anti-programmed death protein (anti-PD1)/anti-programmed death-ligand 1 (anti-PD-L1) directed immunotherapy has shown initial promise in Merkel cell carcinoma and radiation might augment immune responses. We present a case report of a 70-year-old male who underwent resection of Merkel cell carcinoma of the right thigh with a close margin and positive right inguinal involvement. Due to high-risk features, the patient was treated with adjuvant radiation to the right groin and with systemic carboplatin/etoposide, but developed local failure requiring salvage surgical resection. The patient then developed metastatic disease with biopsy proven retroperitoneal involvement refractory to doxorubicin/cyclophosphamide chemotherapy. The patient was then transitioned to single-agent pembrolizumab with a partial response for 10 months until developing progressive disease involving the left inguinal and left external iliac nodal regions. The progressive left inguinal/pelvic disease was treated with conventionally fractionated intensity modulated radiation therapy to a dose of 45 Gy delivered in 25 fractions. Following radiation therapy, the patient had complete response of all sites of disease throughout the body by RECIST criteria. At 20 months post-radiation, the patient remains on pembrolizumab without evidence of disease on imaging. Herein, we present a case of durable abscopal response of metastatic Merkel cell carcinoma treated with concurrent radiation and pembrolizumab, providing evidence that radiation might improve systemic responses to anti-PD1/PD-L1 directed immune therapy. Ongoing prospective trials evaluating the utility of radiation in conjunction with immunotherapy for Merkel cell carcinoma are anticipated to provide clarity on the frequency and durability of abscopal responses when radiation is combined with immune checkpoint inhibitors.